Penggunaan CONUT Score sebagai Prediktor Komplikasi Pasca Pem-bedahan Kanker Kolorektal di RSUP Prof. Dr. R. D. Kandou Manado - Sundah, Hendry; Mambu, Toar; Tjandra, Ferdinand; Sapan, Heber B.; Sumanti, Winfrid M. (UNIVERSITAS SAM RATULANGI, 2019)
Abstract: Nutritional status is one of the factors that influence the metabolic and physiological conditions. Cancer patients, especially colorectal cancer (CRCA), will suffer from decreased nutritional status during their sickness. CONUT score is beneficial to evaluate the nutritional and immunity status of the patients and has been proved to correlate with post operative complications and length of stay. This study was aimed to evaluate the relationship between CONUT score and postoperative complications in CRCA patients. This was an analytical observational study with a cross sectional design. Subjects were 38 patients of CRCA that underwent operation and were admitted at Surgery Inpatients Installation of Prof. Dr. R. D. Kandou Hospital Manado. The result of logistic regression analysis indicated that there was a significant correlation between CONUT score and the risk of complication. The higher the CONUT score, the higher the risk of complication. The determination of complication diagnostic value based on CONUT score was obtained by using ROC curve. The ROC analysis showed that the AUC of CONUT score was 0.977 >0.700 and the cutoff point of CONUT score was 5.5. Patients with CONUT score >5.50 had a tendency to get postoperative complications with the sensitivity of 86.6%, specifity of 95.6%, and accuracy of 94.74%. Conclusion: CONUT score can be used as a screening method to predict the occurence of postoperative complications in CRCA patients.Kata kunci: colorectal cancer, CONUT score, postoperative complicationsAbstrak: Salah satu faktor yang memengaruhi keadaan metabolik dan fisiologik ialah status nutrisi. Penderita kanker terlebih kanker kolorektal (KKR) akan mengalami pengurangan nutrisi selama perjalanan penyakit. CONUT score bermanfaat untuk mengevaluasi status gizi dan imunitas pasien serta terbukti berkolerasi dengan komplikasi serta jumlah hari rawat di rumah sakit pasca pembedahan. Penelitian ini bertujuan untuk mengetahui hubungan CONUT score dengan komplikasi pasca pembedahan KKR. Jenis penelitian ialah analitik obser-vasional dengan desain potong lintang. Subyek penelitian ialah 38 pasien KKR yang menjalani operasi dirawat di Instalasi Rawat Inap Bedah RSUP Prof. Dr. R. D. Kandou Manado. Hasil analisis regresi logistik menyatakan terdapat hubungan yang sangat bermakna antara CONUT score dan kejadian komplikasi. Hubungan ini menyatakan bahwa makin tinggi CONUT score makin besar risiko terjadinya komplikasi. Penentuan nilai diagnostik kom-plikasi berdasarkan CONUT score diperoleh melalui kurva ROC. Berdasarkan analisis ROC diperoleh AUC CONUT score 0,977 >0,700. Hasil analisis ROC memperoleh titik potong CONUT score = 5,5. Pasien dengan CONUT score >5,50 memiliki kecenderungan mengalami komplikasi dengan sensitivitas 86,6%, spesifitas 95,6%, dan nilai akurasi 94,74%. Simpulan: CONUT score dapat digunakan sebagai metode skrining untuk memrediksi terjadinya komplikasi pasca pembedahan kanker kolorektal.Kata kunci: karsinoma kolorektal (KKR), CONUT score, komplikasi pasca pembedahan